Novel Genes Implicated in Embryonal, Alveolar, and Pleomorphic Rhabdomyosarcoma: A Cytogenetic and Molecular Analysis of Primary Tumors - Myriam Goldstein (Neoplasia: An International Journal for Oncology Research, 2006)
Rhabdomyosarcoma, the most common pediatric soft tissue sarcoma, likely results from deregulation of the skeletal myogenesis program. Although associations between PAX3, PAX7, FOXO1A, and RMS tumorigenesis are well recognized, the entire spectrum of genetic factors underlying RMS development and progression is unclear. Using a combined approach of spectral karyotyping, array-based comparative genomic hybridization (CGH), and expression analysis, we examined 10 primary RMS tumors, including embryonal, alveolar, and the rare adult pleomorphic variant, to explore the involvement of different genes and genetic pathways in RMS tumorigenesis. A complete karyotype established for each tumor revealed a high aneuploidy level, mostly tetraploidy, with double minutes and additional structural aberrations. Quantitative expression analysis detected the overexpression of the AURK4 gene in all tumors tested, suggesting a role for this mitotic regulator in the aneuploidy and chromosomal instability observed in RMS. Array-based CGH analysis in primary RMS tumors detected copy number changes of genes involved in multiple genetic pathways, including transcription factors such as MYC-related gene from lung cancer and the cytoskeleton and cell adhesion-encoding genes laminin γ-2 and p21-activated kinase-1. Our data suggest the involvement of genes encoding cell adhesion, cytoskeletal signaling, and transcriptional and cell cycle components in RMS tumorigenesis.